Do audit committee attributes affect firm performance of Sri Lankan firms? / Pratheepkanth Puwanenthiren - Puwanenthiren, Pratheepkanth (Universiti Teknologi MARA, Shah Alam: Accounting Research Institute (ARI), 2020)
This study intended to examine the association between audit committee (AC) attributes and firm performance in Sri Lanka. The research analysed a sample of 100 firm listed in Colombo Stock Exchange (CSE), Sri Lanka for the period 2014-2018. Regression analysis was used to estimate the assocaition between AC attributes and performance. The outcomes revealed that AC attributes of firms, namely AC size, AC independence and AC financial expertise are significantly correlated to firm performance while there is no statistical significant impact of AC size on Tobin's Q. An exception was AC meetings which had an insignificant impact on both performance measures (ROA and Tobin's Q). In conclusion, the results suggest that more active (i.e., more independent members, members with accounting background and a high frequency of meetings) ACs lead to improvement in the effective monitoring mechanism of the firm which indicates that firms can possibly enhance their performance by executing good governance of the firm. Thus, effort should be made to look at this research in a more elaborate viewpoint and across the countries. The effect of AC attributes on firm performance should fully examined in future research.